Prevalence of Clinically Relevant Germline BRCA Variants in a Large Unselected South African Breast and Ovarian Cancer Cohort: A Public Sector Experience - Van der Merwe, Nerina C.; Combrink, Herkulaas MvE; Ntaita, Kholiwe S.; Oosthuizen, Jaco (Frontiers in Genetics, 2022)
Breast cancer is a multifaceted disease that currently represents a leading cause of death in women worldwide. Over the past two decades (1998 – 2020), the National Health Laboratory Services Human Genetics Laboratory in central South Africa screened more than 2 974 breast and/or ovarian cancer patients for abnormalities characteristic of the widely known familial breast cancer genes, Breast Cancer gene 1 (BRCA1) and Breast Cancer gene 2 (BRCA2). Patients were stratified according to the presence of family history, age at onset, stage of the disease, ethnicity, and mutation status relative to BRCA1/2. Collectively, 481 actionable (likely- to pathogenic) variants were detected in this cohort among the different ethnic/racial groups. A combination of old (pre-2014) and new (post-2014) laboratory techniques was used to identify these variants. Additionally, targeted genotyping was performed as translational research revealed the first three recurrent South African pathogenic variants, namely BRCA1 c.1374del (legacy name 1493delC), BRCA1 c.2641G>T (legacy name E881X), and BRCA2 c.7934del (legacy name 8162delG). This initial flagship study resulted in a cost-effective diagnostic test that enabled screening of a particular ethnic group for these genes. Since then, various non-Afrikaner recurrent variants were identified that were proven to represent recurrent variants. These include BRCA2 c.5771_5774del (legacy name 5999del4) and BRCA2 c.582G>A, both Black African founder mutations. By performing innovative translational research, medical science in South Africa can adopt first-world technologies into its healthcare context as a developing country. Over the past two decades, the progress made in the public sector enabled a pivotal shift away from population-directed genetic testing to the screening of potentially all breast and ovarian cancer patients, irrespective of ethnicity, family history, or immunohistochemical status. This modification to the screening methods complies with international standards and guidelines aimed at universal healthcare for all, including people who cannot afford diagnostic testing. This article shares all the cohort stratifications and the likely- to pathogenic variants detected.